The Effect of The End of The Covid-19 Outbreak on The Economy of Msmes In Surakarta City - Farah Dina Eka Putri; Sapta Mei Budiyanto (Journal Research of Social Science, Economics, and Management, 2023)
This study aims to determine the effect of the end of the Covid-19 outbreak on the economy of MSMEs (Micro, Small and Medium Enterprises) in Surakarta City. This research method is a qualitative method with a descriptive approach. Data were collected through participatory observation, in-depth interviews and document studies. The informants in this study consisted of MSME owners (Micro, Small and Medium Enterprises), MSME workers (Micro, Small and Medium Enterprises) and other MSME (Micro, Small and Medium Enterprises) actors. The results showed that the Covid-19 pandemic had a significant negative impact on the economy of MSMEs (Micro, Small and Medium Enterprises) in Surakarta City. These vary, including a decrease in the income of MSMEs (Micro, Small and Medium Enterprises), an increase in the unemployment rate, cancellation of business projects, an increase in costs, a reduction in the number of employees, and an increase in business bankruptcies. Proposed solutions to address this problem include social protection, tax reduction, and infrastructure development. Hail's research is expected to provide important information for the government, entrepreneurs and workers of MSMEs (Micro, Small and Medium Enterprises) about the negative impact of the end of the Covid-19 outbreak on the economy of MSMEs (Micro, Small and Medium Enterprises) in Surakarta City, and assist the government in determining the right strategy to promote the economy of MSMEs (Micro, Small and Medium Enterprises) in the regions.